Factor Analysis of Pad Rice Input Production in Pematang Pulai Village, Sekernan Muaro District, Jambi District - Bangun Joko Laksono; Uliya; Ratna Dewi (International Journal of Scientific Multidisciplinary Research, 2023)
This research was conducted in Pematang Pulai Village, Sekernan District, Muaro Jambi Regency from March 11, 2020 to March 28, 2020. The analysis used in this research is descriptive qualitative and quantitative analysis presented in the table. Furthermore, to analyze the results of the data used Stochastic Frontier Analysis (SFA).Based on the results of the study, it was found that the influence of the use of lowland rice farmers' production factors in Sekernan District, Muaro Jambi Regency was: 1). The land area of 0.63521862 and the workforce of 0.044675791 gave a positive effect, while the seeds of -0.30512884, fertilizer of -0.28402427 and pesticides of -0.12713943 had a negative effect. This shows that the factors of land area and labor have a significant effect on lowland rice production in Pematang Pulai Village, Sekernan District, Muaro Jambi Regency, 2). Efficiency The use of production factors to the production of lowland rice farming in Sekernan District, Muaro Jambi Regency is a technical efficiency of 99.00%